The Conceptual Levels and Theory Languages of Interaction Design - Saariluoma, Pertti (Human Technology, 2021)
In a way, concepts are like friends. Tell me what your concepts are and I can tell what you are. Modifying freely the way Wittgenstein (1921) expressed this important Kantian (1781) point on the limiting power of concepts on one’s thinking, the concepts that human– technology interaction designers of different scientific backgrounds use differ from each other and, consequently, they are apt to solve the same tasks in different ways.